Optimalisasi Branding UMKM Olahan Belimbing Wuluh Sebagai Produk Unggulan Di Sambiarum - Cherryl Tasya Puspita Sari; Tedy Dwi Yuliansya; Virginia Mandasari; Ayundha Evanthi; Susi Hardjati (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The Belimbing Wuluh MSME is one of the leading SMEs in Sambiarum which produces food and beverages made from starfruit, Some of the processed products are nastar, mochi, and syrup. The Belimbing Wuluh SMEs sell their products only when they receive orders or are made by order, so public awareness or brand awareness of the presence of these SMEs still tends to be low. If you look at the current conditions, the problems that arise for Belimbing Wuluh SMEs still do not have a business identity. For this reason, the solution is to rebrand starting from the logo, packaging, and product photos, this is done to introduce their identity. Business identity is very important for business progress with logos, packaging, and product photos as one of the important elements in the application of branding. Branding has a purpose in terms of marketing a product, branding can show product quality that can be trusted and make consumers familiar with the brand. This study uses qualitative methods by conducting observations and interviews. The branding project aims to make products more known with their characteristics and stick in the minds of consumers in order to increase competitiveness and high sales.